Counseling Strategies to Reduce Bullying Behavior in School: A Systematic Literature Review - Alwi Pramana Putra; Nor Mita Ika Saputri; Asmaryadi Asmaryadi; Erlina Harahap (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2026)
Background: Bullying behavior in schools remains a serious issue that negatively affects students' psychological well-being, social relationships, and academic achievement. School guidance and counseling services are considered strategic interventions for preventing and reducing bullying by fostering empathy, emotional regulation, and prosocial skills. Aim: This study aims to conduct a systematic literature review of counseling strategies used to reduce bullying behavior in school settings. Method: A systematic literature review (SLR) was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The reviewed articles were obtained from Sinta-indexed journals, Scopus, and Google Scholar, and published between 2019 and 2024. A total of 20 empirical studies met the inclusion criteria and were analyzed thematically. Result and Discussions: The findings indicate that cognitive-behavioral counseling, empathy-based group counseling, and integrative school-wide counseling programs are effective in reducing aggressive behavior and enhancing students' social-emotional competencies. Furthermore, the effectiveness of counseling interventions is strongly influenced by counselor competence, institutional support, and program sustainability. Conclusions: These findings provide evidence-based recommendations for school counselors and educational institutions to design comprehensive, sustainable bullying prevention programs.